An Overview of Air Traffic and Effective Air Traffic Control Strategies for Istanbul Airport - İsmail Demirhan; Abit Balın; Abdullah Okumuş (Journal of Transportation and Logistics)
This study addresses the significant changes in air transportation for Turkey with the opening of Istanbul Airport and investigates the advantages and disadvantages brought about by the new airport. Previously; providing a service for Istanbul, Atatürk Airport had a limited capacity in terms of air transportation resulting in a mostly ineffective use of time and resources. Thus; this study points out how İstanbul Airport solves the problems experienced previously problems with the expectations of being a solid contender for Turkey in today’s modern aviation. In this paper, a brief explanation of how aviation reached its current place is given and numerical data are provided to further clarify the enormous growth of civil aviation both for Turkey and globally. Subsequently, the role of Istanbul Airport for Turkish civil aviation has been explained in depth. In the light of this information, strengths and weaknesses are identified first, and then opportunities and weaknesses are presented (SWOT analysis) specifically for Istanbul Airport. In the final part of this paper, the importance of new applications through aviation systems has been evaluated briefly to better understand how it positively effects companies, air traffic control units and how it shapes the future of air transportation systems. We believe that the analysis given in four sub-sections will give us a clear understanding of the pros and cons of Istanbul Airport. Considering those assumptions and taking relevant actions it will be easier to make optimum use of the whole system in the airport and to compete with other rivals in the aviation industry.